2017
DOI: 10.1289/ehp1015
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Select Phenols and Phthalates and Respiratory Health in Five-Year-Old Boys: A Prospective Study

Abstract: Background:Phenols and phthalates may have immunomodulatory and proinflammatory effects and thereby adversely affect respiratory health.Objective:We estimated the associations between gestational exposure to select phthalates and phenols and respiratory health in boys.Methods:Among 587 pregnant women from the EDEN (Etude des Déterminants pré et post natals du développement et de la santé de l’Enfant) cohort who delivered a boy, 9 phenols and 11 phthalates metabolites were quantified in spot pregnancy urine sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
4
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 39 publications
5
75
4
8
Order By: Relevance
“…Our results also agree with the cross‐sectional associations found between MCOP, MCNP, and MCPP and asthma in participants aged 18 and over in the 2005‐2006 NHANES study . However, a French birth cohort study found no association between prenatal urinary concentrations of these chemicals and asthma or FEV 1 at age 5 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results also agree with the cross‐sectional associations found between MCOP, MCNP, and MCPP and asthma in participants aged 18 and over in the 2005‐2006 NHANES study . However, a French birth cohort study found no association between prenatal urinary concentrations of these chemicals and asthma or FEV 1 at age 5 …”
Section: Discussionsupporting
confidence: 89%
“…35 However, a French birth cohort study found no association between prenatal urinary concentrations of these chemicals and asthma or FEV 1 at age 5. 36 Our study found many null associations, which could indicate a true lack of association or low power to detect associations due to low sample size. Specifically, unlike several other studies, 12 we did not find associations of in utero exposures to DEHP, BBzP, or BPA and probable asthma or allergy risk.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this prospective cohort with lower phthalate exposure than similar previously reported cohorts [7,8,12,18,19] we found no consistent associations between prenatal phthalate exposure and allergic outcomes in the offspring aged 5 years. Interestingly, prenatal DiNP and DEHP exposure tended to increase the risk of rhinitis, although not statistically significant.…”
Section: Discussioncontrasting
confidence: 83%
“…Phthalates have short biological half-lives from hours to a few days, but because exposure is ubiquitous, exposure levels may be relatively constant [5,6]. We identified 14 prospective cohort studies [5,[7][8][9][10][11][12][13][14][15][16][17][18][19] examining the association between prenatal phthalate exposure and asthma or allergy. Findings are inconsistent probably because different metabolites have been measured and the age of the children varied.…”
Section: Introductionmentioning
confidence: 99%